2019
DOI: 10.1038/s41526-019-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

The gravity dependence of pharmacodynamics: the integration of lidocaine into membranes in microgravity

Abstract: To realize long-term manned space missions, e.g. to Mars, some important questions about pharmacology under conditions of different gravity will have to be answered to ensure safe usage of pharmaceuticals. Experiments on the International Space Station showed that the pharmacokinetics of drugs are changed in microgravity. On Earth, it is well known that the incorporation of substances into cellular membranes depends on membrane fluidity, therefore the finding that membrane fluidity is gravity dependent possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…For example, the fluidity of cell membranes is increased in microgravity (Sieber et al ., 2014) that affects membrane proteins’ functionality, such as membrane channel conductance (Sieber et al ., 2016; Kohn et al ., 2017). Due to the increase in membrane fluidity, drugs’ pharmacokinetic (incorporation of amphipathic drugs into membranes) are changed in microgravity (Kohn and Hauslage, 2019). It is also observed that the bacterial virulence, pathogenicity and resistance to antibiotics increase in space microgravity conditions (Wilson et al ., 2008).…”
Section: Space Environmental Factors Inducing Evolutionary Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fluidity of cell membranes is increased in microgravity (Sieber et al ., 2014) that affects membrane proteins’ functionality, such as membrane channel conductance (Sieber et al ., 2016; Kohn et al ., 2017). Due to the increase in membrane fluidity, drugs’ pharmacokinetic (incorporation of amphipathic drugs into membranes) are changed in microgravity (Kohn and Hauslage, 2019). It is also observed that the bacterial virulence, pathogenicity and resistance to antibiotics increase in space microgravity conditions (Wilson et al ., 2008).…”
Section: Space Environmental Factors Inducing Evolutionary Changesmentioning
confidence: 99%
“…Higher concentrations of antibiotics are required to inhibit bacterial growth in microgravity. This is probably due to the lower transport rate (mass transport is limited to diffusion) and changes in cell proliferation, membrane permeability, rate and morphology (Klaus et al ., 1997, 2004; Kacena and Todd, 1999; Sieber et al ., 2014; Zea et al ., 2016, 2017; Kohn et al ., 2017; Aunins et al ., 2018; Kohn and Hauslage, 2019). In a study with the halophilic archaeon, Haloarcula argentinensis under simulated microgravity condition (clinostat), an increase in the activity of antibiotic efflux pumps resulting in the development of multi-drug resistance to antibiotics, such as augmentin, norfloxacin, tobramycin and cefoperazone was observed (Thombre et al ., 2017).…”
Section: Experiments In Space and Ground-based Space Simulation Facilmentioning
confidence: 99%
“…This supports a membrane‐mediated effect for at least part of lidocaine's action. The effect on anti‐arrhythmic and local anaesthetic actions is not known, but further implies that pharmacodynamics may change in microgravity …”
Section: Pharmacological Conundrumsmentioning
confidence: 99%
“…Lastly, it is important to consider both pharmacokinetic and pharmacodynamic aspects of drugs in space which has also featured in several excellent reviews (Zea 2015;Kast et al 2017;Braddock et al 2019a;Blue et al 2019b). A further recent study has investigated the effect of gravity on the integration of the anesthetic lidocaine into plain lipid membranes (Kohn and Hauslage 2019). In μG, it was shown that the induced increase in membrane fluidity associated with lidocaine incorporation is small when compared with 1 g controls suggesting that incorporation of amphipathic drugs is changed.…”
Section: Space Medicine and Drug Stabilitymentioning
confidence: 99%